Influence of the fractures after falls on the functional abilities of institutionalized and non-institutionalized elderly - Garção, Diogo Costa (2021)
In view of the increase in the elderly population and the increasing persistence of falls in old age, the purpose of this study was to investigate the influence of fractures caused by falls on the functional abilities of non-institutionalized and institutionalized elderly people. One hundred elderly people of both genders, with a mean age of 76 years and who had a history of fractures due to falls in the upper or lower limbs participated in this research. Among the individuals, 50 (30% male and 70% female) lived in community residences, that is, collective shelters, and 50 (30% male and 70% female) lived in long-term care facilities. Initially, the elderly were recruited through medical records from a public hospital and, after the initial contact, the Functional Independence Measure - FIM scale was applied, asking them about the performance of functional skills before and after the falls. Statistical analysis was performed using the chi-square test (p ≤ 0.05). Significant associations were observed between groups when comparing all functional skills studied before and after falls, however, when comparing data on functional skills after falls between non-institutionalized and institutionalized elderly, no significant association was found. The results suggest that fractures caused by falls interfere with the functional independence of the elderly and that the institutionalization factor does not influence functional recovery in the studied sample.